Characterization of sound enamel and natural white spot lesions - Araujo, Erika Michele dos Santos; Vidal , Cristina de Mattos Pimenta; Freitas , Anderson Zanardi de; Wetter , Niklaus Ursus; Matos, Adriana Bona (Brazilian Dental Science, 2022)
Objective: To compare optical, morphological, chemical, and physical aspects of the sound enamel and white spot lesions (WSL) classified as ICDAS 2. Material and Methods: Seventeen human molars with one surface presenting WSL and a sound surface (2 x 2 mm window) were characterized by Quantitative light-induced fluorescence (QLF®), Optical coherence tomography (OCT), microhardness, and Raman spectroscopy. The ANOVA and Tukey’s test were used at 5% significance level. Results: The QLF comparison between distinct substrates yielded decreased Q (integrated fluorescence loss) of -15,37%mm2 and -11,68% F (fluorescence loss) for WSL. The OCT detected mean lesion depth of 174,43 um. ANOVA could not detect differences in the optical attenuation coefficient between the substrates (p>0.05). Lower microhardness measures were observed in WSL than on sound enamel (p<0.05). The Raman spectra showed four vibrational phosphate bands (v1, v2, v3, v4), where the highest peak was at 960.3 cm-1 (v1) for both substrates. However, a 40% decrease in phosphate (v1) was detected in WSL. The peak at 1071 cm-1 was higher for sound enamel, indicating the presence of a phosphate band instead of the B-type carbonate. The spectra showed higher intensity of the organic composition at 1295 cm-1 and 1450 cm-1 for WSL. Conclusion: Non-invasive QLF, OCT and Raman spectroscopy were able to distinguish differences in fluorescence, optical properties, and organic/inorganic components, respectively, between sound enamel and WSL, validated by the destructive microhardness analysis. KEYWORDS Dental caries; Dental enamel; White-spot lesions; Diagnosis; Raman Spectroscopy.